Programy społecznej odpowiedzialności biznesu jako element strategii przedsiębiorstwa - Bem, Kornelia (Annales. Etyka w Życiu Gospodarczym, 2008)
During the last several years we have witnessed heightened interest in the issue of CSR, whichhas been frequently raised at numerous conferences. In addition, a growing number of enterprises havebecome increasingly aware of the relevance of socially responsible actions and begun including them inthe conducted business activity. CSR is gradually becoming an integral part of the company strategy.It is best demonstrated in companies with a large share of foreign capital, where Polish subsidiariesadopt patterns from the parent companies.In the first two parts, the paper outlines the programs of CSR, their key elements and premises,as well as introduces the importance of the company strategy.The final part attempts to convince the reader that along the development of the CSR concept,a gradual process of converting theory into practice is taking place. The CSR programs are becomingan important element of the business strategy. Companies, bigger ones in particular, have begun to takeaccount of the strategies closely interlinked with the very CSR programs.